Sedimentation Handling Model Of Sediment Reservoir On Darma Reservoir Das Cimanuk – Cisanggarung Kuningan Regency - Abdul Khamid (International Conference on Coastal and Delta Areas, 2017)
Reservoir is a water reservoir in a watershed which is used to irrigate agricultural land, fisheries, water regulator (flood controller), watershed catchmentdams channeled by outlet (river) to the reservoir so as not to flow and stagnant in places beneath it and used for drinking water, as well as tourism. As one of the efforts to overcome the flood, it is necessary to revitalize the water structures as a shelter for rainfall runoff and sediment storage building.This research took a case study at Darma Reservoir. In this study, the analysis was performed using Hydrologic Engineering Center-River Analysis System (HEC-RAS). Based on the simulation results of the existing conditionflow, there is a water runoff at River Station (RS) 10 and RS 9. Hence, the design of sediment reservoir building is performed by using Homogeneous Dam as a prevention of overflowing in Darma Reservoir leading to Cisanggarung watershed. The calculation of water potential is based on Rainfall data, while irrigation water demand is calculated based on irrigation total area, water requirement standard for rice plant and crops, industrial water requirement standard based on BWRP Guidelines, Dit.Jen SDA, drinking water requirement standards based on Dinas Cipta Karya and the standard of fishery needs based onDirectorate of Irrigation. One benefit from the calculation of water discharge is for flood control. Measure to be able to control the overflow of river water so it is not too abundant at certain times that can cause flood is to know how much value of the water discharge. The conditions of water that remain in control can be profitable for the fishing business there. The calculation of the discharge can also indicate a response due to changes in bio-geophysical characteristics that occur in a watershed (by watershed management activities) or changes (seasonal or yearly fluctuations) of the local climate. It can later be useful for the subsequent management of the watershed in accordance to the law of natural balance (ecology) which ultimately creates environmental sustainability. The maintenance of watershed ecology is very beneficial to keep the fishery business running in this water body because the ecosystems in it live with supportingconditionfactors (Asdak 1995). Keywords: Reservoir, DAS. Sedimentation, HEC- RAS